Media and ICT use during Covid-19 work from Home Arrangement - Separa, Lenis Aislinn Chua; Gapasin, Anna Ruby P.; Ponsaran, John N. (Universitas Semarang, 2023)
Introduction: The Covid-19 pandemic caused educational institutions to temporarily suspend face-to-face classes. This led university lecturers to immediately shift to work from home mode in teaching students and collaborating with colleagues which made them adjust their work routine into online mode. Since this phenomenon entailed unique experiences based on the context of lecturer and students, this study aims to know the role of media and information communication technologies on the work from home experiences of a university lecturer during the Covid-19 pandemic. Methods: A case study of a university lecturer was conducted through a written interview. Questions that solicit information on feelings about working from home, descriptions of the tasks needed to do in a usual day of a lecturer working online, and challenges encountered in teaching during the pandemic. Codes, categories and themes were generated in the data analysis. Findings: Results reveal that home was perceived as a comfort zone for the university lecturer during the time of pandemic. The use of social media, email, and video conferencing platforms were based on three aspects: (1) the intention for communication; (2) the importance of materials involved, and (3) the assessment of fitness to work context. Originality: This project provides understanding of lived experiences of a university lecturer during the Covid-19 pandemic and how technology plays a role in teaching and learning based on the context of their uses. The piece can be used as a scaffolding of future studies that intends to look at emerging relationships between humans and technology.